ANALISIS DETERMINAN RETURN SAHAM PERUSAHAAN PUBLIK SUBSEKTOR TRANSPORTASI - Hasti Putri Hulu (Owner : Riset dan Jurnal Akuntansi, 2023)
The Covid-19 pandemic has had a negative market reaction in almost all sectors of the economy. But the transportation and logistics sector gave a positive market reaction with a surge in the stock price index which increased by 213%. This requires investors to provide an adequate assessment of the destination company to assess the possibility of obtaining capital gain or capital loss before deciding to invest. Stock return is one of the indicators used in evaluating the destination company. In order to be able to evaluate stock returns, several variables such as earnings per share, price earning ratio, price to book value, debt to equity ratio, return on assets, and net profit margin are thought to influence stock returns. This study aims to see the effect of earnings per share, price earning ratio, price to book value, debt to equity ratio, return on assets, and net profit margin on stock returns in the transportation subsector. This study uses data on 11 public companies in the transportation subsector listed on the IDX from December 2018 to December 2021 using multiple regression statistical analysis. The results of this study indicate that the price earning ratio has a negative and significant effect on stock returns, while the price to book value has a positive effect on stock returns. Earning per share variable, debt equity ratio, return on assets, and net profit margin have no significant effect on stock returns